Building Superior Human Resources: An Educational Approach to Early Marriage Generation Z in Pegayut Village - Trisnawati; Sabeli Aliya; Dewi Sartika; Afrida Wati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to increase the understanding of the younger generation in Pegayut Village about the importance of awareness regarding early marriage, as well as reducing the divorce rate caused by this phenomenon. Data was collected through surveys and in-depth interviews that explored the factors that encourage early marriage, including individual, family, poverty, and social and cultural environments. Methods for implementing activities include outreach through counseling, question and answer sessions, and discussions. The activity participants were 300 teenagers from Pegayut Pemulutan Village aged between 14 and 19 years. The research results show that public understanding of the negative impacts of early marriage is still low, so more intensive education and outreach efforts are needed to reduce the divorce rate due to early marriage and improve the quality of Human Resources in Pegayut Village.